Cassia afrofistula, Kenyan Cassia - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS)
The Kenyan cassia can be used as a showy ornamental tree or shrub, with its dark foliage and bright yellow flowers. Some people find the seed pods to be unattractive and prune the tree after it flowers to prevent pods from developing. This tree tolerates a wide range of soil types and can be used in a garden, park, patio, or streetscape setting. This 2-page fact sheet was written by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, and published by the UF Department of School of Forest Resources and Conservation, July 2012.